The Higher Education Fund: Unconventional Financing Strategies for Public Universities in Bangladesh - Sarkar, Shakhawat Hossain; Hossain, Syed Zabid (Bangladesh Journal of Educational Research, 2026)
This study appraises Bangladesh’s higher education financing based on primary data. Empirical results reveal that state funding, rather than tuition fees, is the primary source of higher education finance. In addition to state funding, several supplementary sources ought to be considered, such as establishing rapport with domestic and international studentship benefactors, encouraging faculty members to pursue research projects and research grants, managing low‑interest and accessible student loans, introducing a modest education tax on alums, companies, and affluent individuals, creating academic and research collaborations with overseas higher education institutions, initiating financially beneficial projects, and introducing unconventional shifts funded by students themselves. The government, higher education institutions, students, alums, private employers, the social elite, corporate firms, foreign fund providers, and other stakeholders are invited to collaborate in creating a Higher Education Fund. Revenue from all sources is to be deposited into the fund, and all higher education expenses can be met from it, in accordance with fund‑accounting rules. This collaborative approach ensures that all stakeholders are valued and included in higher education financing.